Unveiling Atopic Dermatitis: Exploring Smoking, Obesity, and Fast Food as Pivotal Risk Factors - A Systematic Review - Hibatullah, Faiz Nur; Kalada, Elisabeth Chelsea Uma; Baita, Etina Noor; Putra, Fabianus Yvan Marino Cahaya; Adiwinoto, Ronald Pratama; Prasetya, Hanung (Indonesian Journal of Medicine, 2024)
Background: Atopic dermatitis (AD), also known as Eczema, is an inflammatory skin disease that causes dry, itchy skin. several risk factors for AD have been reported including demographics, socioeconomics, active and passive smoking, urbanization, diet, breastfeeding and timing of introduction of solid foods, obesity, physical exercise, fast food, and environmental air pollution. This study aims to better understand the effect of smoking, obesity, and fast food consumption as one of the risk factors of AD. Subjects and Method: Systematic review with the help of PICOs to search for eligible articles. Articles were searched from 3 different databases (PubMed, ScienceDirect, and Google Scholar) with the help of a search engine application, Publish or Perish (PoP), using the following keyword: “smoking AND atopic dermatitis”, “fast food AND atopic dermatitis”, “obesity AND atopic dermatitis”. Results: 10 articles matched the specified inclusion and exclusion criteria for this study. Whether or not smoking causes AD is still conflicting, few studies reported there is no correlation between smoking and AD, whereas other studies said otherwise. In contrast to that, second-hand smoke was found to be affecting AD conditions more (up to 2.320). Most of our eligible articles reported that obesity did cause severe reactions of AD up to 1.62 times. Frequent fast food consumption was also found to be causing severe AD conditions (OR=1.580). Conclusion: Obesity and fast food consumption are one of the causes of AD development and AD severity. The risk factor of cigarette smoking still conflicts with whether or not it affects AD conditions.